PENGARUH PENGGUNAAN MEDIA DOMINO FLASH CARD TERHADAP KETERAMPILAN BERHITUNG SISWA KELAS V SD 060843 - Nasution, Amirah Fadhil Ramadhaini; Rezeky, Desfira Sari; Fitri, Anisya; Nabila, Miranda; Sitepu, Melyani Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to evaluate the effect of using Domino Flash Card media on the numeracy skills of grade 5 students at SD 060843. The flash card media used has a size of 8x5 cm, with the front side containing multiplication questions and the back side containing the answers. The research method involves a pretest and posttest to measure the increase in students' numeracy skills after using this media. The research results show that the use of flash card media significantly improves students' numeracy skills, which can be seen from the comparison of pretest and posttest scores which show a significant increase. In addition, this media creates an interactive and fun learning atmosphere, which contributes to increasing student motivation and involvement in the learning process. This research supports previous findings showing that visual media, such as flash cards, can increase the effectiveness of mathematics learning. Thus, the use of flash card media can be an effective alternative in teaching mathematics in elementary schools, helping students not only with their calculation skills but also in building their confidence in facing mathematics problems